2021
DOI: 10.1177/07311214211028619
|View full text |Cite
|
Sign up to set email alerts
|

Who Are Gun Owners in the United States? A Latent Class Analysis of the 2019 National Lawful Use of Guns Survey

Abstract: We used data from the 2019 National Lawful Use of Guns Survey to segment the gun-owning population into different subcultural categories. Performing a latent class analysis, we introduce six types of indicators: (1) the types of firearm owned, (2) the reported primary reason for owning a firearm, (3) involvement in various gun-related activities, (4) Second Amendment activism, (5) the extent to which those in one’s social network own guns, and (6) measures of symbolic meanings attached to firearms. We introduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 106 publications
(121 reference statements)
1
4
0
Order By: Relevance
“…The results demonstrated that pro‐gun beliefs, peer risk factors, and weapon carrying could be utilized to group individuals into unique classes in a large sample of middle and high school students from rural Pennsylvanian schools. These results support findings that suggest that adolescent weapon carrying, peer risk factors, and pro‐gun beliefs are heterogenous but can be grouped into unique patterns as suggested by previous research (Boine et al, 2021; Ellyson et al, 2022). Multinomial logistic analyses also identified factors that increased or decreased the odds of class membership.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results demonstrated that pro‐gun beliefs, peer risk factors, and weapon carrying could be utilized to group individuals into unique classes in a large sample of middle and high school students from rural Pennsylvanian schools. These results support findings that suggest that adolescent weapon carrying, peer risk factors, and pro‐gun beliefs are heterogenous but can be grouped into unique patterns as suggested by previous research (Boine et al, 2021; Ellyson et al, 2022). Multinomial logistic analyses also identified factors that increased or decreased the odds of class membership.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, several gun researchers have utilized probability‐based analyses to identify subgroups of gun usage based on more individual‐level traits. For instance, Boine et al (2021), identified gun culture subgroups using a mixture of psychological and behavioral traits (i.e., gun type, motivation for owning a gun, activities, social network, meaning of guns, and other gun‐related behavior; Boine et al, 2021). Their analysis produced six subgroups (i.e., family protectors, incidental gun owners, second amendment activists, target shooters, hunters, and self‐protectors) in which participants in each subgroup clustered around central gun beliefs and behaviors as well as race and gender (Boine et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firearm owners are diverse in multiple ways, including their reasons for ownership, engagement in Second Amendment activism, frequency of firearm handling, and connection to the social aspects of "gun culture" (Boine et al, 2020(Boine et al, , 2021Schleimer et al, 2020). Firearm storage practices and views on voluntary, temporary out-of-home storage vary across groups of firearm owners (Bryan et al, 2020;Salhi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…7 See Boine et al (2022), Blithe and Lanterman (2022), Carlson (2015Carlson ( , 2020, Joslyn (2020), Mencken and Froese (2019), and Yamane (2017). 8 See, for example, Bunn (2022), Peyser (2020), Raskin (2023), Sanchez (2023), and Tavernise (2021).…”
Section: Demographic Trends and The Politics Of Representationmentioning
confidence: 99%